THE ROLE OF "PAGUYUBAN REMAJA PEDULI HIV/AIDS SIDOARJO" (PARPAS) ON KNOWLEDGE, ATTITUDE, AND ACTION FOR HIV/AIDS PREVENTION IN SENIOR HIGH SCHOOLS IN SIDOARJO - Adelia Dwi Pratiwi; Windhu Purnomo (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2020)
There were total of 2,100,000 new HIV infections worldwide and 1,500,000 deaths from AIDS recorded in 2013. The total HIV/AIDS cases in 2017 in Sidoarjo reached 476 cases and cumulatively reached 1,245 cases. HIV/AIDS is a well-known topic among teenagers. Teenagers are often associated with physical development in puberty phase which usually followed by sexual development. Furthermore, they also experience changes emotionally and physically which are projected in their behavior and attitude.  These circumstances make teenagers prone to the risky behavior towards HIV/AIDS transmission. This study aims to analyze the role of "Paguyuban Peduli HIV/AIDS Sidoarjo" or PARPAS on teenagers' knowledge, attitude, and behavior towards HIV/AIDS prevention. This research is an observational analytic using cross-sectional research design. The population of the study is all students of SMAN 1 Taman and SMAN 1 Sidoarjo, 2,370 students in total. The sampling technique uses simple random sampling and the sample size is 100 students. The result shows that there is correlation between PARPAS role on knowledge and attitude of students' in Sidoarjo towards HIV/AIDS prevention. Nevertheless, there is no correlation between PARPAS role on students' behavior towards HIV/AIDS prevention. Suggestions concluded from the results are including early detection, attempt in joining organization related to HIV/AIDS awareness, and health education given to both students and parents.